Theoretical Model of Possibility of 15-minute City in Urban Planning Using the Meta-Synthesis Method - Hafez Mahdnejad (توسعه پایدار شهری)
The 15-minute city model focuses on urban planning based on the needs and preferences of citizens, encouraging short trips and neighborhood-based activities. Based on this, the aim of the current research is theoretical model presentation of the 15-minute city realization as the proximity of activities and walkability model in urban planning. The current research is developmental-applied type and its method is qualitative with an emphasis on Meta-synthesis method. The statistical community includes all the researches conducted regarding 15-minute city model in the period from 2016 to 2022. The sample size includes 38 articles and documents that were selected based on the ten principles of the Critical Assessment Skills Program. First, 123 sources were found, Then 35 sources were removed by examining the title. 22 sources were removed by abstract screening. In the next step, the content of 66 sources was analyzed in terms of content and quality, and finally, 38 articles were selected for final analysis. Time analysis of research sources shows that the highest frequency is related to 2022, which is equivalent to 47% of the sources. About 81% of the sources are related to the years 2022 and 2021. 16% of the selected sources are related to the years 2020 and 2019. In terms of sources typology, 79% of the sources are scientific articles. In terms of the research type, the number of quantitative, qualitative and mixed researches is 21, 13 and 4 respectively.. The results show 79 extracted codes in seven categories are classified. These seven categories are: pillars (proximity, density, diversity and ubiquity), basic functions, digitalization revolution, environmental considerations and climate change, adaptive infrastructures, cohesion and social inclusion, and quantitative indicators. The value of the Kappa index (0.761 at a significance level of 0.000) indicates the appropriate reliability of the research results (above 0.6).